MANAJEMEN STRATEGI MENINGKATKAN KUALITAS PENDIDIKAN DI YAYASAN AL IHSAN KEBAGUSAN JAKARTA SELATAN - Aprilliantoni, Aprilliantoni; Pasaribu, Muhammad Syafaruddin; Irwansyah, Saripudin (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Quality education will enable a country to develop rapidly. Achieving quality education requires an effective management strategy. Strategic management includes the processes of planning, organizing, leadership, and controlling to achieve organizational goals. In the context of education, strategic management plays a crucial role in determining the direction and priorities for the development of educational institutions, as well as in the optimal allocation of resources to achieve educational goals. This study aims to analyze the implementation of strategic management in efforts to improve the quality of education at Yayasan Al Ihsan Kebagusan, South Jakarta. This research uses a qualitative descriptive approach with a case study method. The results show that Yayasan Al Ihsan has implemented several managerial strategies, including improving teaching quality through teacher training, strengthening learning facilities, and increasing parental involvement in children's education. However, challenges in human resource management and financing need to be addressed in order to achieve optimal educational goals. This study concludes that the effective implementation of strategic management can play a significant role in improving the quality of education at Yayasan Al Ihsan, but regular evaluations should be conducted to adapt to changing needs and challenges.